High-Entropy Oxide Derived from Metal–Organic Framework as a Bifunctional Electrocatalyst for Efficient Urea Oxidation and Oxygen Evolution Reactions - Fereja, Shemsu Ligani; Zhang, Ziwei; Fang, Zhongying; Guo, Jinhan; Zhang, Xiaohui; Liu, Kaifan; Li, Zongjun; Chen, Wei (ACS applied materials & interfaces, 2022)
High-entropy oxides (HEOs) offer unique features through a combination of incompatible metal cations to a single crystalline lattice. Owing to their special characteristics such as abundant cation compositions, high entropy stabilization, chemical and thermal stability, and lattice distortion effect, they have drawn ever-increasing attention for various applications. However, very few studies have been reported for catalytic application, and developing HEOs with large surface areas for efficient catalytic application is still in infancy. Herein, we design nanostructured HEO of (FeNiCoCrCu)3O4 using metal–organic frameworks (MOFs) as sacrificial templates to achieve a large surface area, high density of exposed active sites, and more oxygen vacancies. Single-crystalline phase HEOs with surface area as large as 206 m2 g–1 are produced and further applied as bifunctional electrocatalysts for the urea oxidation reaction (UOR) and oxygen evolution reaction (OER). Benefiting from enhanced oxygen vacancies and a large surface area with abundant exposed active sites, the optimized HEO exhibited excellent electrocatalytic activity toward UOR with a very low potential of 1.35 V at the current density of 10 mA cm–2 and showed long-term stability for 36 h operation, making a significant catalytic performance over previously reported HEOs. Moreover, the HEO demonstrated an efficient catalytic performance toward OER with a low overpotential of 270 mV at 10 mA cm–2 and low Tafel slope of 49 mV dec–1. The excellent catalytic activity is ascribed to the starting MOF precursor and favorable high-entropy effect.